Dispositivos de reconhecimento da identidade quilombola na política pública brasileira: o selo quilombos do Brasil - Silva, Thacya Clédina da (2022)
In contemporary contexts, in which sociopolitical, environmental, territorial and identity values become strategic in the social construction of markets, initiatives to create recognition devices become relevant. In this thesis, we address the Selo Quilombos do Brasil (QB) within the scope of discussions on the recognition of social identities through affirmative public policies, with special attention on access to production and consumption circuits. To understand the creation of this device, its implementation and the repercussions it had for the communities involved, we start from the historicity of quilombola identity construction in Brazil, marked by centuries of racial and social stigmatization, until reaching the developments of affirmative policies aimed at Afro-Brazilians in recent years. decades. We understand that the sociopolitical dimension of identities evokes a field of disputes over social meanings that affect agents of the State, markets and the perceptions that subjects and groups construct about themselves. In this way, the issue that permeates the development of this work is related to the themes of the quilombola agenda on the public agenda, mainly the processes of socio-productive inclusion in market contexts strongly conditioned by the dynamics of material and symbolic consumption, in which the creation of recognition devices, like the Selo QB, play strategic roles. Therefore, we asked about the meanings produced by this seal within the quilombola communities that used it and with the mediators linked to the bodies that implemented it. Therefore, the objectives of this research were to understand the creation of the QB Seal, in the trajectory and historical context that led to the implementation of the main public policies for Brazilian quilombola communities; identify with the mediators of government bodies and entities representing the quilombola communities involved in the creation of the QB Seal, the meanings they attributed to them; investigate whether the QB Seal served as a device that allowed the quilombola communities that used it to access markets and expand their social recognition; and, finally, understand the meanings that subjects in quilombola communities attributed to this device and how these meanings impacted their self-recognition of identity. The methodological approach used bibliographic and documentary research, fieldwork and semi-structured interviews with quilombola communities in Bahia and Alagoas. Mediators from government bodies and entities representing quilombola communities involved in the creation of the QB Seal were also interviewed. The main results of the research indicate that the seal promoted meanings, beyond the mere purpose of identifying the origin of a product, which provide feelings of recognition and visibility of the production and existence of quilombola communities. Despite the criticisms that can be made regarding the execution of the public policy that sought to implement the QB seal, its access by communities and the growing activism of ethnic and political consumption in Brazil, seem to represent potential for promoting anti-racist practices, with greater socioeconomic and social inclusion. symbolic of quilombola production and existence. Currently, however, the main challenges seem to be maintaining sociopolitical recognition and maintaining the quilombola agenda on the country's government public policy agenda.